JURIDICAL REVIEW OF AUTOMATION TECHNOLOGY WITHIN THE LEGAL FRAMEWORK OF THE CREATIVE ECONOMY: EMBRACING OPPORTUNITIES OR FACING CHALLENGES? - Bayu Mogana Putra; Muhammad Alifian Fauzannasa Nawawi (Jurnal Yuridis, 2025)
This study aims to provide a juridical analysis of the integration of automation technology within the legal framework of the creative economy in Indonesia, with a specific focus on the use of Point of Sale and Enterprise Resource Planning systems. Automation technology is increasingly recognized as a vital tool for enhancing efficiency, transparency, and professional business management in the creative industry. However, the rapid advancement of such technologies has not been fully matched by adequate legal certainty, particularly within the existing creative economy regulations. This research employs a normative legal method with a conceptual and statutory approach, supported by content analysis of relevant policy documents and literature. The findings indicate that, although the regulatory framework acknowledges the importance of technological utilization, normative gaps remain concerning the governance of digital automation particularly in areas such as data protection, system-based labor relations, and equitable access to technology. Using the lens of law and economics, this study emphasizes the need for regulations that promote innovation while maintaining a balance between economic efficiency and social justice. The results have practical implications for policymakers, especially in designing responsive implementing regulations that accommodate digital transformation within the creative economy sector. The study recommends the formulation of specific legal instruments for automation technologies and the enhancement of digital literacy programs for creative economy actors as strategic measures to address future challenges